A Sinc Function Analogue of Chebfun. - Richardson, M; Trefethen, L (2011)
Chebfun is an established software system for computing with functions of a real variable, but its capabilities for handling functions with singularities are limited. Here an analogous system is described based on sinc function expansions instead of Chebyshev series. This experiment sheds light on the strengths and weaknesses of sinc function techniques. It also serves as a review of some of the main features of sinc methods, including construction, evaluation, zerofinding, optimization, integration, and differentiation. © 2011 Society for Industrial and Applied Mathematics.